Using learning objects that promote understanding of mathematical knowledge: good practices in secondary education - Beatriz ARELLANO SÁNCHEZ; Jorge Antonio ALFARO RIVERA; María Soledad RAMÍREZ MONTOYA (Ediciones Universidad de Salamanca, 2014)
The objective of this research was to analyze the skills developed in students and how do the processes of construction of geometrical knowledge using learning objects (LO) for math three high school students are improved. The research question was: which skills did the students develop when they were using learning objects and how was their geometrical understanding process improved? The methodology used was a mixed approach. Results showed that the use of learning objects effectively develops student's skills in communication and computing. Promoting further understanding of geometry concepts. It is concluded that OA act as tools to assist the student in understanding geometry thereby promoting the use of technology for educational purposes.